PERTUMBUHAN PERUSAHAAN MEMODERASI PENGARUH PROFITABILITAS DAN KEPEMILIKAN ASING TERHADAP TRANSPARANSI PENGUNGKAPAN SUKARELA LAPORAN TAHUNAN - Eben Ezer Pasaribu (2021)
This study aims to see the company's growth moderates the effect of profitability and foreign ownership on the transparency of voluntary disclosures in the annual report. The population in this study are all companies in the Basic Materials sector listed on the Indonesia Stock Exchange in the 2017 to 2019 period. The sample used is 102 samples with purposive sampling method. Profitability is measured by profitability, Foreign Ownership is measured by the percentage of foreign ownership in the company. Company growth is measured by asset growth for the current year, while the Transparency of Voluntary Disclosure in the Annual Report uses a voluntary disclosure checklist. The analytical method in this study uses descriptive analysis and multiple linear regression analysis hypothesis testing with the help of STATA 16. The results in this study indicate that, simultaneously profitability and foreign ownership affect the transparency of the voluntary disclosure of the annual report. Partially, profitability and foreign ownership have no effect on the transparency of the voluntary disclosure of the annual report. The company's growth does not moderate profitability and foreign ownership of the transparency of the voluntary disclosure of the annual report.